Measurements and assessment of sound emitted by toys intended for children below 3 years old - Beata GRYNKIEWICZ-BYLINA; Bożena RAKWIC (Archives of Acoustics, 2015)
Toys emitting sounds are classified as significant sources of noise found in the children environment. Impulse and continuous noise emitted by toys, used in close to the child’s ear, acting directly on the organ of hearing, can lead to serious adverse health effects. This is especially true for children under the age of three, in which the state of the hearing organ determines their intellectual development.